Initiatives to address leprosy as a human rights issue through the mandate of UN Special Rapporteur: Achievements and challenges - Takahiro Nanri (Public Library of Science (PLoS), 2022)
Leprosy, or Hansen's disease, is one of the oldest infectious diseases in the world. It has long been associated with stigma and discrimination, but only in recent years has this aspect been formally recognized by the international community as a human rights issue. The UN Human Rights Council first adopted a resolution on leprosy in 2008, and this was later followed by a UN General Assembly resolution in 2010. Nonbinding principle and guidelines on elimination of discrimination against persons affected by leprosy and their family members accompanied the 2010 resolution, but these have yet to be fully implemented. In 2017, the Human Rights Council appointed a Special Rapporteur on leprosy to investigate the extent to which the principles and guidelines have been implemented, and her term was extended for a further 3 years in 2020. Considering the proper implementation of the principles and guidelines to be key to eliminating the discrimination that persons affected by leprosy and their families face in various parts of the world, this paper looks at the contribution the Special Rapporteur can make. Based on an assessment of her activities to date, it concludes that the Special Rapporteur has actively worked to build networks with persons affected by leprosy and related organizations and gain their trust, but has faced challenges in organizing official country visits. It goes on to analyze what sort of legacy the Special Rapporteur should aim to leave behind after completing her second term and how she can go about doing so in the time remaining. To this end, it makes 5 suggestions: (1) gather information systematically on the actual situation of discrimination; (2) compile a collection of success stories; (3) ensure that there is consistency between legally binding international covenants and treaties and the principles and guidelines; (4) present proposals for concrete actions that can be taken after the Special Rapporteur's second term ends; and (5) initiate a feasibility study on creating an "index" and "indicators" to measure the current status of stigma and discrimination and the extent to which the principles and guidelines have been implemented.